Right ventricular morphology and the onset of dyspnea: the MESA-right ventricle study. - Michael R Kaufmann; R Graham Barr; João A C Lima; Amy Praestgaard; Aditya Jain; Harikrishna Tandri; David A Bluemke; Steven M Kawut (PLoS ONE)
Background The association of right ventricular (RV) structure and function with symptoms in individuals without cardiopulmonary disease is unknown. We hypothesized that greater RV mass and RV end-diastolic volume (RVEDV), smaller RV stroke volume (RVSV), and lower RV ejection fraction (RVEF) measured by cardiac magnetic resonance imaging (MRI) in participants free of clinical cardiovascular disease at baseline would be associated with a greater risk of self-reported dyspnea. Methods The Multi-Ethnic Study of Atherosclerosis (MESA) performed cardiac MRIs on participants without clinical cardiovascular disease between 2000 and 2002. We excluded subjects who reported "prevalent" dyspnea at the first assessment (24 months). The presence of dyspnea was assessed at 24 months, 42 months, and 60 months from baseline. Cox proportional hazards models were used to examine the relationship between RV measures and incident dyspnea. Results In the final study sample (N = 2763), there were significant interactions between RV measures and sex in terms of the risk of dyspnea (p<0.05). Among men (N = 1453), lower RV mass (p = 0.003), smaller RVEDV (p<0.001), smaller RV end-systolic volume (RVESV) (p = 0.03) and decreased RVSV (p<0.001) were associated with an increased risk of developing dyspnea after adjusting for covariates. Associations remained after adjusting for left ventricular function and lung function. However, there were no significant associations between RV measures and the risk of dyspnea in women. Conclusions Lower RV mass and smaller RV volumes were associated with an increased risk of dyspnea in men, but not in women.